Group for antiwar MDs broadens focus, hopes to attract new members. - Martin, M (1996)
Physicians for Global Survival (Canada), formerly known as Canadian Physicians for the Prevention of Nuclear War, has changed its name and broadened its mission in an effort to increase membership. The group's international interests include banning antipersonnel land mines and having the threat or use of nuclear weapons declared illegal. In Canada, it has supported gun-control legislation and been involved in assessing the effect of military training flights on the Innu of Labrador. The president-elect Dr. Konia Trouton of the University of Calgary, says the association is the "ethical voice of the medical profession in its concern for social justice."